An assessment of the mutation patterns in South African isolates of Potato leafroll virus and the expression of recombinant viral coat protein genes in Escherichia coli - Rothmann, Adri Hilda (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc)--University of Stellenbosch, 2007.